2011
DOI: 10.1111/j.1600-0625.2011.01303.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue microarray analysis of RANKL in cutaneous lupus erythematosus and psoriasis

Abstract: Recently, it was discovered that the receptor activator of nuclear factor jB (RANK) ⁄ RANK ligand (RANKL) is part of an important signal transduction pathway for tissue homoeostasis. Therefore, we were interested in investigating RANKL expression in the epidermis of skin lesions from patients with different subtypes of cutaneous lupus erythematosus (CLE) and psoriasis as well as normal healthy donors. Using the tissue microarray technique, skin biopsy specimens were evaluated by immunohistochemistry. RANKL sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Notch gene expression has been reported in mouse and sheep skin during follicle initiation (8)(9)(10)(11). However, as Cre-mediated disruption of Notch signalling in fetal mouse epidermis did not inhibit follicle formation (10,12), its involvement, if any, must be through its action in the mesenchyme.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…Notch gene expression has been reported in mouse and sheep skin during follicle initiation (8)(9)(10)(11). However, as Cre-mediated disruption of Notch signalling in fetal mouse epidermis did not inhibit follicle formation (10,12), its involvement, if any, must be through its action in the mesenchyme.…”
Section: Conflict Of Interestsmentioning
confidence: 99%
“…Background Environmental factors such as ultraviolet (UV) light have been identified to contribute to the activation of inflammatory and autoimmune diseases of the skin such as cutaneous lupus erythematosus (CLE) (1)(2)(3)(4)(5). UV irradiation induces various effects in the skin of CLE patients, such as cell death and inflammation (6)(7)(8), and several molecules, such as type I and III interferons (IFNs) and myxovirus protein A (MxA), an IFN-induced human protein expressed in CLE skin lesions, have been shown to be important biomarkers in the pathogenesis of the disease (9-13).…”
Section: Accepted For Publication 21 April 2014mentioning
confidence: 99%
“…Toberer et al [12] found a significantly increased RANKL expression in psoriatic epidermis, while it was not observed in the patients with cutaneous lupus erythematosus. This could be explained by Treg functional insufficiency in psoriatic skin lesions that resulted in decreased effector T cell inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that RANKL plays a significant role in regulation of numerous functions of the dendritic cells (DCs), such as enhancement of T cell activation capacity, increased release of proinflammatory cytokines, and prolonged cell survival. Moreover, RANKL is expressed on inflamed or activated keratinocytes and it induces activation of epidermal Langerhans cells (LCs) [12]. …”
Section: Introductionmentioning
confidence: 99%